FACTORS AFFECTING CUSTOMER RETENTION IN BATAM HARBOUR BAY CGV CINEMAS - Nanda harry Mardika (Universitas Putera Batam, 2022)
This study aims to determine the factors that influence customer retention in CGV. Total of respondents were used in this study were 96 respondents by using purposive sampling technique. The data processing technique used descriptive analysis and multiple linear regression analysis which was processed by using SPSS program. The results showed that customer retention was proven to be positively and significantly influenced by service quality and location. The calculated t value for the service quality variable (X1) -0.747 with a significance value of 0.457 and the t count for the location variable (X2) 4.315 with a significance value of 0.000. The results of the Anova table show that the calculated F value is 14,780 with a significance value of 0.000. The conclusions of this study are (1) service quality has a negative and insignificant effect on customer retention , (2) location has a positive and significant effect on customer retention , and (3) service quality and location simultaneously have a positive and significant effect on customer retention.